Pembuatan Feed Instagram Menggunakan Aplikasi Canva Sebagai Media Promosi Pada Business Wisdom Institute - Muhammad Farhan Fathoni; Tri Ramadani Arjo (PT. Hasba Edukasi Mandiri, 2025)
Instagram Feeds are very important content in digital promotional activities. The Business Wisdom Institute is a training service institution that uses Instagram in its business promotion activities; however, the content presented is not interesting and informative enough so the Instagram insights are not effective enough. The aim of the research was to create Feed content as an attractive, informative and unique promotional media on the Instagram Business Wisdom Institute with the help of the Canva Application. The research method used was action research with the research procedures consisting of planning, action, observation and reflection. The questionnaires were distributed to 30 respondents, namely 1 Owner, 2 design experts, 2 marketing expert and 25 potential consumers. Based on the results of the analysis of questionnaire distribution, the EPIC Rates score was found to be in the Very Effective area in both the Emphaty dimension, Persuasion, Impact and Communication. This shows that the Feed content design is very effective as promotion content on the Instagram business Wisdom Institute. In a study, two data can be used, namely using primary sources and secondary sources. Data Sources are anything that can provide information about related research. In collecting data sources, researchers collect data sources in the form of primary data and secondary data The conclusion of this research is that Feed content designs created with the Canva Platform can be effective and informative promotional content. It is recommended that the Business Wisdom Institute be consistent and strive to always update the design and related information in the Feed content on the Business Wisdom Institute’s Instagram.